Tác động của dịch COVID-19 đến hiệu quả hoạt động của ngân hàng thương mại Việt Nam - Nguyen Thi Thuy , Huong; Nguyen Huu , Huan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The stability of the banking system is threatened by the consequences of the COVID-19 pandemic as the non-performing loan increase, banks’ revenue decrease, and risks of businesses’ bankruptcy. Customers’ deposits become deficit while the demand for loans decreases, which affects Vietnamese commercial banks. This study aims to estimate the efficiency of Vietnamese banking system before and during the COVID-19 period by using Data Envelopment Analysis model to evaluate the impact of the COVID-19 pandemic. Furthermore, the Tobit regression is applied for investigating the main determinants that influence the banking industry in Vietnam during the COVID-19 pandemic. Our findings suggest that the COVID-19 pandemic has a negative impact on the technical efficiency, pure technical efficiency, and scale efficiency of 31 Vietnamese commercial banks. Additionally, this study indicates the days of social distancing in Vietnam impact the performance of the banking system.
Keywords: Bank efficiency; COVID-19 pandemic